Neuroprotective Effects of Extracts from the Radix Curcuma aromatica on H2O2-induced Damage in PC12 Cells - Liu, Juxiang; Zhang, Lianli; Liu, Dan; Li, Baocai; Zhang, Mi (Combinatorial Chemistry & High Throughput Screening, 2018)
Aim & Objectives: Curcuminoids are characteristic constituents in Curcuma, displaying obviously neuroprotective activities against oxidative stress. As one of the Traditional Chinese Medicines from Curcuma, the radix of Curcuma aromatica is also rich in those chemicals, but its neuroprotective activity and mechanism remain unknown. The aim of the current study is to evaluate the neuroprotective effects of extracts from the radix of C. aromatica (ECAs) on H2O2-damaged PC12 cells. Material and Methods: The model of oxidative stress damage was established by treatment of 400 μM H2O2 on PC12 to induce cell damage. After the treatment of ECWs for 24 h, the cell viability, LDH, SOD, CAT and GSH were measured to evaluate the neuroprotection of ECAs on that model. The potential action mechanism was studied by measurement of level of ROS, cell apoptosis rate, mitochondrial membrane potential (MMP), morphologic change, the intracellular Ca2+ content (F340/F380) and the expressions of Bcl-2, Bax and Caspase-3. Additionally, the constituents from tested extracts were analyzed by HPLC-DAD-Q-TOF-MS method. Results: Compared with a positive control, Vitamin E, 10 μg/ml of 95% EtOH extract (HCECA) and 75% EtOH extract (MCECA) can markedly increase the rate of cell survival and enhance the antioxidant enzyme activities of SOD, CAT, increase the levels of GSH, decrease LDH release and the level of ROS, attenuate the intracellular Ca2+ overloading, reduce the cell apoptotic rate and stabilize MMP, down-regulate Bcl-2 expression, up-regulate Bax and caspase-3 expression, and improve the change of cell morphology. The chemical analysis showed that diarylheptanoids and sesquiterpenoids are the major chemicals in tested extracts and the former were richer in HCECA and MCECA than others. Conclusions: These findings indicated that the effects of HCECA and MCECA on inhibiting the cells damage induced by H2O2 in PC12 are better than other extracts from the radix of C. aromatica, and the active constituents with neuroprotective effects consisting in those two active extracts are diarylheptanoids.
Keywords: HPLC-Q-TOF-MS anaysis